2015
DOI: 10.1111/ffe.12307
|View full text |Cite
|
Sign up to set email alerts
|

An extrapolation method to determine the effective notch stress in welded joints

Abstract: This paper presents the development of an extrapolation method to estimate the notch stress in welded steel joints, in line with the effective notch stress concept described in the International Institute of Welding guideline. The proposed approach provides a convenient method to determine the local notch stress at the weld toes without the need to model a finite notch radius as required in engineering guidelines, which creates significant modeling challenges in the numerical procedure, especially for 3‐D join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Pradana et al have shown that for full‐penetration welded cruciform joints, the stress fields from the sharp and rounded notch ( r ref = 1 mm) converge at a distance about 2% of the plate thickness from the weld toe, as illustrated in Fig. a.…”
Section: The Extrapolation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pradana et al have shown that for full‐penetration welded cruciform joints, the stress fields from the sharp and rounded notch ( r ref = 1 mm) converge at a distance about 2% of the plate thickness from the weld toe, as illustrated in Fig. a.…”
Section: The Extrapolation Methodsmentioning
confidence: 99%
“…The computation of a C value for a specific X‐joint requires (1) FE model with a ‘sharp’ toe that provides A and B values and (2) FE model with a ‘rounded’ toe that computes the ENS according to the IIW 2 procedure. Figure b illustrates the one‐eighth FE model used for the brace axial tension cases, as well as the typical mesh at both ‘rounded’ and ‘sharp’ weld toe, where the element sizes follow the recommendation by Pradana et al The model simulates the X‐joint using 20‐node brick elements with reduced integration (C3D20R) in the ABAQUS element library. Both the base metal and the weld (AWS CJP profile) adopt the same linear‐elastic material model with a Young's modulus of 205 GPa and a Poisson ratio of 0.3.…”
Section: Numerical Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Methods for calculating the fatigue life of notched components can be divided into local and non-local. [19][20][21][22][23] The non-local methods take into account the influence of the stress gradient and define a zone which is considered as equivalent and in which significant fatigue processes take place. The first is global, where calculations are performed based on nominal stress, external forces and fatigue notch factor K f .…”
Section: Introductionmentioning
confidence: 99%